Analysis of Tocopherols by High Performance Liquid Chromatography - B. Edison (E-Journal of Chemistry)
: Gas chromatography is the key technique for organic components and also for tocopherols analysis. High performance liquid chromatography has an important role to take part in applications such as the handling of less usual samples, prevention of degradation of heat sensitive functional groups and for micro preparative purposes. Many approaches for development of improved methods are suggested, especially for reversed phase applications.